An animal experimental study on the intravitreal injection of ranibizumab as an adjunctice treatment in retinoblastoma - Abd Aziz, Nor Azimah (2015)
Objective: To determine the efficacy of intravitreal ranibizumab injection in rabbit induced with retinoblastoma and to determine the potential side effect of intravitreal ranibizumab injection in rabbit induced with retinoblastoma Methodology: Retinoblastoma was induced in 6 New Zealand White rabbit by subretinal injection of cultured WERI-Rb cell line into the right eye. After six week, Group A (n=3) was given intravitreal ranibizumab injection (0.5mg) and Group B (n=3) as control group. Baseline and serial clinical examination was performed at day 1, 3, 6, 12, 15, 18, 21. The right eyes were enucleated on day 21 and sent for histopathological examination. Results: All rabbits developed intraocular tumour in the subretinal/retinal and vitreous cavity detectable via fundus examination started after one week post tumour inoculation. The tumour grew slowly without evidence of spontaneous regression. After intravitreal ranibizumab injection in Group A (treated group), there was slight regression of the tumour detected clinically while the tumour in the group B (control group) continued to grow slowly. Histopathological finding confirmed presence of tumour that closely resembled features of poorly differentiated human retinoblastoma cells. The tumour in the control group was larger compare to the treated group. The treated group however also developed focal area of retinal hyperplasia. There was no significant side effect of ranibizumab injection except temporary high intraocular pressure immediate post injection which relieved after paracentesis. Conclusion: Intravitreal injection ranibizumab (0.5mg) caused regression of tumour in this xenograft rabbit model clinically. However, the result was not statistically significant. There was temporary increase in intraocular pressure immediately post injection which relieve with paracentesis. Therefore, it was considered as a safe therapy.